Preventivni protidopinški programi v Sloveniji - Makuc, Nina (Šport (Ljubljana), 2020)
The recent doping affairs in Slovenia and abroad testify that doping has become a problem of all of society, not only elite athletes. For this reason, preventive anti-doping programmes must be designed as broadly as possible to include the entire population in specific phases, not only promising and elite athletes. Through basic values in sport people can be taught from early childhood about the meaning of fair play, honesty, compliance with the rules, etc., all of which will be useful for them later in life, regardless of whether they engage in sport on a competitive or recreational level. Slovenians are undoubtedly a "sporting nation", which is why it is even more important to implement a long-term national prevention programme for sport without doping, which should be well-conceived from scratch. In recent years, the Slovenian Anti-Doping Organisation (SLOADO) has put a greater emphasis on prevention programmes which include not only professional athletes but also primary school pupils, recreational athletes and the entire sporting public. The results of their activity will most probably be seen only after a longer period of regular implementation of this systematic programme. However, we dare say that step by step SLOADO, together with the Slovenian Olympic Committee and other national sports associations, has been creating a new generation of Slovenian athletes who will not use prohibited substances in their sports career.
Keywords: antidoping; anti-doping; awareness-raising; doping; education; informiranje; izobraževanje; ozaveščanje; sharing information; Slovenian Anti-Doping Organisation; Slovenska antidoping organizacija; šport; values; vrednote